A novel cell-based immunofluorescence assay for the detection of autoantibodies to myelin-associated glycoprotein - Mariotto, Sara; de Gaspari, Piera; Jäger, Dominik; Hahn, Stefanie; Forni, Cindy; Saschenbrecker, Sandra; Lattwein, Erik; Dinoto, Alessandro; Ferrari, Sergio (Frontiers in Neurology, 2023)
Peripheral neuropathy with antibodies to myelin-associated glycoprotein (MAG) is an autoimmune demyelinating disorder of the peripheral nervous system caused by pathogenic IgM recognizing the human natural killer-1 glycoepitope expressed on MAG. This study aimed to analyze the performance of a new indirect immunofluorescence cell-based assay (CBA, EUROIMMUN) for the detection of anti-MAG IgM. Antibody reactivity was determined in sera from 95 patients with clinical and neurophysiological evidence of anti-MAG-associated neuropathy and in control samples from 55 patients with other forms of peripheral neuropathy. Compared to the results of the gold standard method (ELISA, Bühlmann) and using samples at a dilution of 1:100, the CBA had a sensitivity of 98.9% and a specificity of 100% (PPV 100%, NPV 98.2%). In conclusion, the CBA allows the detection of antibodies to MAG using an easy and standardized technique, and it presents a sensitive and specific alternative to the more time-consuming ELISA. Larger studies are needed to address anti-MAG titer monitoring in parallel with clinical activity.